2011
DOI: 10.1002/ejic.201000948
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium(IV) and ‐(V) Complexes of Reduced Schiff Bases Derived from Aromatic o‐Hydroxyaldehydes and Tyrosine Derivatives

Abstract: The reduced Schiff bases of salicylaldehyde and pyridoxal (and o-vaniline)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Hence, a large number of in vitro and in vivo studies have demonstrated that vanadium salts and their well-known complexes have beneficial properties in diseases such as diabetes [4][5][6][7] and cancer [8,9]. Various complexes of oxidovanadium(IV/V) have been synthesized in the past three decades starting from the vanadyl ion and different ligands, such as amino acids, peptides, and Schiff bases, to improve compound stability, solubility, and bioavailability, properties mandatory for their biological effects [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a large number of in vitro and in vivo studies have demonstrated that vanadium salts and their well-known complexes have beneficial properties in diseases such as diabetes [4][5][6][7] and cancer [8,9]. Various complexes of oxidovanadium(IV/V) have been synthesized in the past three decades starting from the vanadyl ion and different ligands, such as amino acids, peptides, and Schiff bases, to improve compound stability, solubility, and bioavailability, properties mandatory for their biological effects [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A copper(II) coordination polymer with tetranuclear copper(II) units [Cu 4 (Sal-SeMet) 4 Á MeOH Á EtOH] as secondary building blocks was confirmed by X-ray crystallographic analysis. This tetranuclear unit is further connected by carbonyl oxygen from the ligand of another tetranuclear unit at the apical position to form a 1-D coordination polymer.…”
Section: Resultsmentioning
confidence: 79%
“…Significant progress for transition metal complexes containing Schiff-base ligands has been achieved due to their applications including biological, clinical, analytical, and industrial in addition to their important roles in catalysis and organic synthesis [1][2][3][4][5][6][7]. However, problems of ligand instability for Schiff bases are often encountered [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account their much higher intrinsic stability and much lower susceptibility toward hydrolysis, several publications were released either with characterization of metal complexes [153,[160][161][162][163][164] or using these very versatile ligands to prepare suitable complexes to prepare metal-based catalytic systems [163,[165][166][167][168][169][170][171][172].…”
Section: Metal Ion-salen Complexesmentioning
confidence: 99%